International joint venture (IJV) directors contribution to board effectiveness: Learning from the literature - Petrovic, Jelena; Kakabadse, Andrew P.; Kakabadse, Nada K. (Emerald, 2006)
This paper provides a comprehensive review of the literature on the governance of international joint ventures (IJVs). Through focusing on IJV boards and top teams, examination of the current debate regarding the IJV director’s contribution to board performance and effectiveness is undertaken and, in so doing, directions for future research are identified. The literature review reveals that little consideration has been paid by researchers to the work of the IJV board and the role and contribution of IJV board directors to board effectiveness. Further, it is concluded that current understanding of IJV board functioning and the ways in which directors of IJV boards contribute to board effectiveness remains incomplete. Apart from highlighting the need for further study into the role and contribution of IJV board directors to board effectiveness, the paper suggests ways in which IJV director contribution and performance could be explored further.
Keywords: International joint venture (IJV); board director; board effectiveness